The Effect of Liprotide-Encapsulated Vitamin D3 on MDA and SOD in Rats Deficient Vitamin D and Calcium - Untari Untari; Gemala Anjani; Faizah Fulyani; Adriyan Pramono; Endang Mahati; Sylvia Rahmi Putri; Reza Achmad Maulana (Faculty of Medicine, Universitas Diponegoro, 2023)
Background: Vitamin D deficiency is frequently correlated with elevated malondialdehyde (MDA) levels and decreased superoxide dismutase (SOD) activity. Several studies have demonstrated that vitamin D3 can reverse intracellular oxidative stress. However, vitamin D is prone to deterioration and instability. Liprotides contain lipids and proteins that can prevent vitamin D from oxidating.Objective: This study aims to investigate the effects of liprotide-encapsulated vitamin D3 on MDA concentrations and SOD activity in calcium and vitamin D-deficient rat models.Methods: The experimental post-test-only control group study used 24 Wistar rats randomly in 4 groups. Groups K(-), K(+), and P were fed a vitamin D and calcium-depleted AIN-93M diet for 14 days. Standard feed AIN-93M was received by normal groups (KN). Groups K- were deficient rats in vitamin D and calcium without intervention. The groups of K+ and P were given vitamin D3 (180 IU) which was non-encapsulated and liprotide-encapsulated for 28 days.The SOD activity was quantified with Superoxide Dismutase (SOD) Activity Assay Kit, while MDA levels were determined using Thiobarbituric Acid Reactive Substance (TBARS) method. The statistical analysis used One-way ANOVA test with Least Significant Difference follow-up test.Results: The MDA levels and SOD activity in the K+ and P groups had significant differences (p<0.05) against the control group. Liprotides-encapsulated vitamin D3 significantly reduced MDA levels and enhanced SOD activity compared to non-encapsulated in rats with a deficiency in vitamin D and calcium.Conclusion: Liprotide-encapsulated vitamin D3 has the potential to increase SOD activity and decrease MDA levels.